2016
DOI: 10.1111/inm.12230
|View full text |Cite
|
Sign up to set email alerts
|

Taking personal responsibility: Nurses' and assistant nurses' experiences of good nursing practice in psychiatric inpatient care

Abstract: Therapeutic nurse-patient relationships are considered essential for good nursing practice in psychiatric inpatient care. Previous research suggests that inpatient care fails to fulfil patients' expectations in this regard, and that nurses might experience the reality of inpatient care as an obstruction. The aim of the present study was to explore nurses' and assistant nurses' experiences of good nursing practice in the specific context of psychiatric inpatient care. Qualitative interviews were conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 41 publications
2
88
0
6
Order By: Relevance
“…In their study involving relationship‐oriented nurses in inpatient mental health care, Gabrielsson et al . () found that the participants were unable to uphold good nursing care due to a malfunctioning practice environment. This meant that the nurses accepted the authority of the physicians, while not taking responsibility and assigning tasks to others.…”
Section: Discussionmentioning
confidence: 99%
“…In their study involving relationship‐oriented nurses in inpatient mental health care, Gabrielsson et al . () found that the participants were unable to uphold good nursing care due to a malfunctioning practice environment. This meant that the nurses accepted the authority of the physicians, while not taking responsibility and assigning tasks to others.…”
Section: Discussionmentioning
confidence: 99%
“…Hamrin et al () point to the impact of creating environments that foster the ability to build therapeutic relationships. In this context, meeting the patient's need instead of following the house rules requires a continuous focus and critical reflection on one's own caring practice, as supported in the work of Espinosa et al (), Gabrielsson et al () and Looi Rpn et al (). In our opinion, professionals should discuss the structural conditions of their professional practice in the mental healthcare context and participate in reorganize their services in line with changes in external conditions to create a secure working environment.…”
Section: Discussionmentioning
confidence: 99%
“…Bang () highlights that organizational culture exists as an inconsistency between defended values such as person‐centred care and lived values such as “distancing themselves” based on experiences of defended values as “overwhelming and too much” (Bachmann et al, ). Gabrielsson, Savenstadt, and Olsson () found in their study that the nurses were unable to improve poor circumstances in nursing practice. They promoted their own survival by refuting or redefining their responsibility.…”
Section: Introductionmentioning
confidence: 98%
“…'Being with' a patient may entail stepping away from health-related tasks for a moment and listening, being open to learning about a patient's situation in a non-judgmental, calm manner [18]. However, it may be hard to be present due to workload, tiredness and competing demands affecting concentration [19]. Likewise, taking a mechanistic approach to care, focusing on technology and technical skills, may put HCPs at risk of disengaging from the patient before them [20], resulting in staff doing for rather than being with patients [21].…”
Section: Discussionmentioning
confidence: 99%